Unraveling the threads: Palm oil, transmigration, and exclusion in Mantadulu, South Sulawesi - Syafaat, Andi Muhammad Batara (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Palm oil plantations and transmigration in Indonesia, implemented since the New Order era until now, aim to boost economic growth with the intended consequence of improving community welfare, particularly for transmigrants and local residents. Methods: This study employed a case study approach focusing on Mantadulu Village in East Luwu Regency, South Sulawesi. Data was collected through secondary sources, including government documents, news articles, and reviews of research results on palm oil plantation expansion and transmigration in Sulawesi. The data was analyzed descriptively, with a focus on the historical context, conflict trajectories, and socioeconomic impacts. Findings: However, this study reveals a contrary outcome; the presence of PTPN XIV in Mantadulu Village, South Sulawesi has resulted in the exclusion of the surrounding community. This, in turn, has led to the confiscation of their production factors, widening the poverty gap for both transmigrants and local communities. The expansion of palm oil plantations, coupled with the transmigration program, created a surplus labor force, potentially leading to worker exploitation and reduced wages. Conclusion: The transmigration program and palm oil plantation expansion in Mantadulu Village have largely failed to improve the welfare of transmigrants and local communities as intended. Instead, these initiatives have increased the risk of poverty through land exclusion and unfavorable farming schemes. Novelty/Originality of this Study: The novelty of this study lies in its focus on the intricate relationship between the transmigration program and palm oil plantation expansion in South Sulawesi, an area often overlooked in existing research. It uniquely highlights the socio-economic conflicts and class dynamics arising from these programs, providing a fresh perspective on the grassroots impacts and conceptual challenges underlying transmigration and agricultural policies in Indonesia.